Analysis and management of methane emissions from dumping pond: A cases study at Felda Jengka palm oil mill / Khairuddin, M.N ... [et al.] - Khairuddin, Mohd Nizar; Sulaiman, A; Syahlan, S; Zulkefli, F; Bula, J; Wan Abdul Rahman, W.M.N; Kassim, J; Md Isa, I; Mat Tahir, M.R (2013)
Palm oil production is major agricultural industry in Malaysia, in which palm oil mill effluent (POME) are considered as major waste. These waste products create a huge amount of treated POME sludge into dumping ponds. This paper will focus on theoretical methane emission from the treated POME sludge and establish the effective management practices. The treated POME sludge was collected from dumping ponds in Felda Jengka 8 palm oil mill. The results showed that the sludge content yield of biogas is 0.18 m3 / kgVS, while methane yield production was 0.15 m3 / kgVS. Total methane emission per dumping pond was 2.92 m3/ha. Indeed, it showed potential contribute for greenhouse gasses emission. Meanwhile, financial viabilities of biogas production and biofertilizer projects was obtained in palm oil mill with and without clean development mechanism (CDM). Biogas is captured from closed digestion tank treating POME sludge and converted to green renewable electricity, while biofertilizer were compared viabilities. The financial analysis for 12 years project term analysis indicated that CDM gave a significant effect and ensured economic viability for both project with 15% of internal rate return (IRR), RM 0.9 million of net present value (NPV) and 5 year of payback period (PBP). It is concluded that biogas production and biofertilizer provide additional opportunities for palm oil mills to utilize biomass by products actively with additional financial support of CDM It is advantageous for the palm oil mills to obtain additional profits through utilizing excess biomass. Furthermore, this technology adaption can improve the surrounding environment by utilized treated POME disposal in optimum used.